Structure of a mammalian sperm cation channel complex - Lin, Shiyi; Ke, Meng; Zhang, Yuqi; Yan, Zhen; Wu, Jianping (Nature (London), 2021)
The cation channel of sperm (CatSper) is essential for sperm motility and fertility 1 , 2 . CatSper comprises the pore-forming proteins CATSPER1–4 and multiple auxiliary subunits, including CATSPERβ, γ, δ, ε, ζ, and EFCAB9 1 , 3 – 9 . Here we report the cryo-electron microscopy (cryo-EM) structure of the CatSper complex isolated from mouse sperm. In the extracellular view, CATSPER1–4 conform to the conventional domain-swapped voltage-gated ion channel fold 10 , following a counterclockwise arrangement. The auxiliary subunits CATSPERβ, γ, δ and ε—each of which contains a single transmembrane segment and a large extracellular domain—constitute a pavilion-like structure that stabilizes the entire complex through interactions with CATSPER4, 1, 3 and 2, respectively. Our EM map reveals several previously uncharacterized components, exemplified by the organic anion transporter SLCO6C1. We name this channel–transporter ultracomplex the CatSpermasome. The assembly and organization details of the CatSpermasome presented here lay the foundation for the development of CatSpermasome-related treatments for male infertility and non-hormonal contraceptives. A structure of the sperm-specific CatSper complex features a number of additional components; together, these components and the CatSper complex are termed the CatSpermasome.